2015
DOI: 10.1186/s13054-015-0819-7
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of surface versus endovascular cooling techniques in cardiac arrest patients: a propensity-matched analysis

Abstract: IntroductionVarious methods and devices have been described for cooling after cardiac arrest, but the ideal cooling method remains unclear. The aim of this study was to compare the neurological outcomes, efficacies and adverse events of surface and endovascular cooling techniques in cardiac arrest patients.MethodsWe performed a multicenter, retrospective, registry-based study of adult cardiac arrest patients treated with therapeutic hypothermia presenting to 24 hospitals across South Korea from 2007 to 2012. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
1
37
1
Order By: Relevance
“…Two retrospective studies have reported non-significant trends to better neurological outcome associated with endovascular cooling compared to surface cooling. One study found good neurological outcomes of 35.4 versus 25.6 % for endovascular versus surface cooling [46]; another, of 45 versus 38 % [47]. Recently, the results of a prospective multicenter RCT in 400 patients comparing endovascular to basic surface cooling methods have been published [48].…”
Section: Start Temperature Managementmentioning
confidence: 99%
“…Two retrospective studies have reported non-significant trends to better neurological outcome associated with endovascular cooling compared to surface cooling. One study found good neurological outcomes of 35.4 versus 25.6 % for endovascular versus surface cooling [46]; another, of 45 versus 38 % [47]. Recently, the results of a prospective multicenter RCT in 400 patients comparing endovascular to basic surface cooling methods have been published [48].…”
Section: Start Temperature Managementmentioning
confidence: 99%
“…None have found statistically significant differences in patient outcomes between different cooling technologies, although some have reported trends in favor of invasive cooling. 11,17,18 Of note, 1 study reported that therapeutic hypothermia in CA patients could be induced and maintained with low-technology methods (refrigerated fluids and ice packs) only, without cooling devices, and that outcomes were comparable to studies using more sophisticated cooling technology.19 However, controlling temperature in this way significantly increases nursing workload, and it is difficult to prevent temperature variation during the maintenance phase and to effectively control rewarming. …”
mentioning
confidence: 99%
“…The numbers are similar to those reported in a fairly large (167 patients) retrospective study from Norway, where survival with good neurological outcome was 38% (surface cooling) versus 45% (core cooling), P=0.345. 17 Similarly, a retrospective study using a Korean registry for CA patients compared 559 patients cooled with surface-cooling devices (including Blanketrol, MediTherm, and Arctic Sun) with 244 patients cooled with endovascular catheters 18 ; good neurological outcome was 25.6% for surface cooling versus 35.4% for endovascular cooling (P=0.01). 18 However, the groups were not well matched; after propensity score matching in 360 patients (180 in each group), rates of favorable neurological outcome were 30% for surface cooling versus 35% for endovascular cooling (P=0.31).…”
mentioning
confidence: 99%
See 2 more Smart Citations